Glucagon-Like Peptide-1 Analog Exendin-4 Ameliorates Cocaine-Mediated Behavior by Inhibiting Toll-Like Receptor 4 Signaling in Mice - Zhu, Changliang; Tao, Hong; Rong, Shikuo; Xiao, Lifei; Li, Xinxiao; Jiang, Shucai; Guo, Baorui; Wang, Lei; Ding, Jiangwei; Gao, Caibing; Chang, Haigang; Sun, Tao; et al. (Frontiers in Pharmacology, 2021)
Exendin-4 (Ex4), a long-lasting glucagon-like peptide-1 analog, was reported to exert favourable actions on inhibiting cocaine-associated rewarding and reinforcing effects of drug-seeking in animal models of addiction. However, the therapeutic potential of different dose of GLP-1 receptor agonist Ex4 in different behavioral paradigms and the underlying pharmacological mechanisms of action are incompletely understood. Herein, we firstly investigated the effects of Ex4 on cocaine-induced condition place preference (CPP) as well as extinction and reinstatement in male C57BL/6J mice. Additionally, we sought to elucidate the underlying pharmacological mechanism of these actions of Ex4. The paradigm of cocaine-induced CPP was established using 20mg/kg cocaine or saline alternately during conditioning, while the reinstatement paradigm was modeled using 10 mg/kg cocaine on the reinstatement day. Different dose of Ex4 was administrated intraperitoneally either during conditioning or during extinction state or only on the test day. To elucidate the molecular mechanism underlying the potential effects of Ex4 on maladaptive behaviors of cocaine, the TLR4-related inflammation within the hippocampus was observed by immunofluorescence staining, and the expression levels of toll-like receptor 4 (TLR4), tumor necrosis factor (TNF)-α, and interleukin (IL)-1β were detected by Western blotting. As a consequence, systemic administration of different dose of Ex4 was sufficient to inhibit the acquisition and expression of cocaine-induced CPP, facilitate the extinction of cocaine-associated reward and attenuate reinstatement of drug-seeking behavior. Furthermore, Ex4 treatment diminished expression levels of TLR4, TNF-α, and IL-1β, which were up-regulated by cocaine exposure. Altogether, our results indicated that Ex4 effectively ameliorated cocaine-taking and seeking behaviors likely through neurobiological mechanisms partly attributable to the inhibition of TLR4, TNF-α and IL-1β in mice. Consequently, our findings improved our understanding of the efficacy of Ex4 for the amelioration of cocaine-induced behavior and suggested that Ex4 may be applied as a drug candidate for cocaine addiction.